Preparation and voltammetric studies of titanium (IV) Phosphate modified with silver hexacyanoferrate to a voltammetric determination of L-cysteine - Cumba, Loanda Raquel [UNESP]; Bicalho, Urquisa de Oliveira [UNESP]; Carmo, Devaney Ribeiro do [UNESP] (My University, 2012)
In this work, a novel Titanium (IV) Phosphate (TiPh) composite was prepared using a easily methodology of the synthesis. A preliminary characterization of the precursor and resulting materials was defined using spectroscopic and voltammetric techniques. As a second step, TiPh was reacted with silver ions (TiPhAg) and subsequent hexacyanoferrate was added (TiPhAgHCF). The electrochemical behaviour of the composite (TiPhAgHCF) was verified by means of a graphite paste electrode using cyclic voltammetry in a potential range of 0.2 to 0.9 V (vs Ag/AgCl). The cyclic voltammogram of the modified electrode containing (TiPhAgHCF) exhibited a single redox couple. The redox couple present a formal potential (E θ') of 0.77 V vs Ag/AgCl (KNO 3 1.0 mol L -1; v = 20 mV s -1) and ascribed to the [Fe II(CN) 6]/[Fe III(CN) 6] processes. In a electroanalytical study, the peak located at 0.77 V present a sensitive response to L-cysteine. The modified graphite paste electrode showed a linear range from 2.0×10 -4 to 9.0×10 -3 mol L -1 for the determination of L-cysteine with a limit detection of 3.34×10 -4 mol L -1 and relative standard deviation of ± 5% (n = 3) and amperometric sensitivity 10.34×10 -3 A mol L -1. The modified electrode was electrochemically stable and showed excellent reproducibility. © 2012 by ESG.
Keywords: Cyclic Voltammetry; L-cysteine; Titanium (IV) phosphate